2015
DOI: 10.1149/06426.0161ecst
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Corrosion of AISI 316L in Chlorosilane Environments at 550°C

Abstract: High temperature chlorosilane gas streams are used throughout the photovoltaic, polycrystalline silicon, and fumed silica industries as a means to purify, refine, and produce silicon species. These gas streams create a unique corrosion environment due the ability of many metals to form metal-silicides or metal-chlorides depending on the atmosphere. In this study, a method was developed to test AISI 316L stainless steel in a high temperature (550°C) chlorosilane environment by exposing the samples to variable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Previous work had shown that 316L in chlorosilane environments can form either metal chlorides or metal silicides depending on the relative amounts of STC and HCl in the system (10). Because metal silicides appear to be more protective than metal chlorides, it was determined that the time and temperature dependence of metal silicide formation in chlorosilane environments is more industrially relevant than metal chloride formation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work had shown that 316L in chlorosilane environments can form either metal chlorides or metal silicides depending on the relative amounts of STC and HCl in the system (10). Because metal silicides appear to be more protective than metal chlorides, it was determined that the time and temperature dependence of metal silicide formation in chlorosilane environments is more industrially relevant than metal chloride formation.…”
Section: Resultsmentioning
confidence: 99%
“…Sample preparation and corrosion exposure was done in accordance to the procedure described in our previous work (10). For completeness, it is briefly described here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the authors have done some work in the field of chlorosilane corrosion of 316L stainless steel. [19][20][21] Again, this work was largely studying the implications of using 316L in chlorosilane environments rather than investigating the specific mechanisms of corrosion. To the best knowledge of the authors, there are no published studies detailing the corrosion mechanisms of iron in chlorosilane environments representative of industrial processes.…”
mentioning
confidence: 99%